Panic! : markets, crises, & crowds in American fiction - Zimmerman, David A. (David Andrew), 1964- (Cultural studies of the United States., 2006)
During the economic depression of the 1890s and the speculative frenzy of the following decade, fiction writers published scores of novels that explored the new cultural visibility of Wall Street, high finance, and market crises. Blending literary, historical, and cultural analysis, Zimmerman investigates how writers turned to fledgling research in mob psychology, psychic investigations, and conspiracy discourse to understand how mass acts of financial reading and popular participation in the corporate transformation of the American economy could trigger financial disaster and cultural chaos.